Yoginī, cult and temples : a tantric tradition - Dehejia, Vidya (New Delhi : National Museum : Sole distributors, Publications Division, 1986)
On yoginīs, minor form of Hindu goddesses belonging to tantric tradition.
Includes index.
Bibliography: p. 228-236.
Mode of access: Internet.
Keywords: Tantrism; Hindu goddesses